Penerapan Metode Diskusi Dalam Meningkatkan Aktivitas Belajar Siswa Kelas X TITL 3 SMKN 1 Sumatera Barat melalui pendekatan CTL - Asrival, Asrival (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the application of the cooperative group discussion learning method in improving the learning achievement of grade X TITL 3 students at SMK Negeri 1 Sumatera Barat in the subject of Islamic Religious Education (PAI) with the topic of avoiding anger (ghadab). The study was conducted in two cycles, involving reflection and improvement based on the results of the previous cycle. The results showed that in cycle II, the students’ learning completeness showed significant improvement, with an absorption rate of 78.38%, exceeding the minimum target of 75%. Students’ activities in cooperative group discussions also increased, as they became more active in understanding concepts and presenting group work outcomes. Although some students did not achieve completeness, overall, this learning method successfully improved students’ academic achievement.